Effect of short-term methylphenidate on social impairment in children with attention deficit/hyperactivity disorder: systematic review - Sarit Alkalay; Orrie Dan (BMC, 2022)
Abstract Attention Deficit/Hyperactivity disorder (ADHD) is one of the most common disorders in school-age children. In addition to learning difficulties associated with the disorder's core symptoms of inattention and hyperactivity, children with ADHD display substantial social impairments. Methylphenidate (MPH) in formulations such as Ritalin or Concerta mitigates inattention and hyperactivity, but the effects of the therapy on social behavior in children with ADHD are not clear. This review aims to determine the effectiveness of short term (up to 6 months) MPH treatment on three domains of social skills in children aged 6-14 with ADHD: (i) Recognition of nonverbal emotional expressions, which are a marker of inherent (unlearned) social understanding, (ii) theory of mind (ToM) components that relate to learned cognition and social communication, and (iii) social competence in everyday environments. 15 relevant studies were identified based on inclusion/exclusion criteria. The results show mixed effects: the overall social performance as evaluated by parents, teachers or peers, and some components of ToM, were found to improve following a weeks-long course of MPH treatment. However, the effects of the medication are less clear when evaluating momentary/nonverbal social responses such as reactions to emotional facial expressions. While the findings of this review indicate that an MPH medication regime of order weeks to months could improve, to a degree, social impairment in children with ADHD, more studies are required to identify the medications' mechanism and confirm such a conclusion.